A sequential bargaining model of the fed funds market with excess reserves - Sam Schulhofer-Wohl; James A. Clouse (Federal Reserve Bank of Chicago, 2018)
We model bargaining between non-bank investors and heterogeneous bank borrowers in the federal funds market. The analysis highlights how the federal funds rate will respond to movements in other money market interest rates in an environment with elevated levels of excess reserves. The model predicts that the administered rate offered through the Federal Reserve's overnight reverse repurchase agreement facility influences the fed funds rate even when the facility is not used. Changes in repo rates pass through to the federal funds rate, but by less than one-for-one. We calibrate the model to data from 2017 and find in an out-of-sample test that the model quantitatively matches the increase in the federal funds rate in the first four months of 2018. The rise in the fed funds rate in 2018 is attributed to movements in repo rates and not to changes in the scarcity value of reserves.
Keywords: 330